Bearing the Dead : the British Culture of Mourning from the Enlightenment to Victoria. - Schor, Esther (Princeton University Press, 2001)
Esther Schor tells us about the persistence of the dead, about why they still matter long after we emerge from grief and accept our loss. Mourning as a cultural phenomenon has become opaque to us in the twentieth century, Schor argues. This book is an effort to recover the culture of mourning that thrived in English society from the Enlightenment through the Romantic Age, and to recapture its meaning. Mourning appears here as the social diffusion of grief through sympathy, as a force that constitutes communities and helps us to conceptualize history. In the textual and social practices of the B.